2016
DOI: 10.1123/ijspp.2015-0406
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Match-Play Characteristics of Elite Rugby League and Indirect Markers of Muscle Damage

Abstract: Match duration, high-intensity running, and collisions were associated with variations in EIMD markers, suggesting that recovery is dependent on individual match demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
102
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(107 citation statements)
references
References 33 publications
5
102
0
Order By: Relevance
“…Therefore, the validity of adopting a single training load measure remains unclear. Given these difficulties, it is regularly suggested that a more robust approach to infer validity is to adopt the changes in training outcomes, such as measures of fatigue [30], injury incidence [14] or physical qualities [2. 28, 29], as the criterion method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the validity of adopting a single training load measure remains unclear. Given these difficulties, it is regularly suggested that a more robust approach to infer validity is to adopt the changes in training outcomes, such as measures of fatigue [30], injury incidence [14] or physical qualities [2. 28, 29], as the criterion method.…”
Section: Introductionmentioning
confidence: 99%
“…However, external load methods have also been found to possess dose-response relationships with training outcomes. For example, total distance (r = 0.86 [95 % CI: 0.70 to 0.95]) and highspeed distance (r = 0.76 [95 % CI: 0.51 to 0.91]) were associated with the changes in creatine kinase concentration 24 h after professional rugby league match play [30]. Therefore, it is likely that both external-and internal-training-load methods can contribute information to the outcomes of training, with the extent likely to change between modes of training [27,36].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the growing use of micro technology incorporating GPS and accelerometers has attempted to quantify external training loads in the form of running (Evans et al, 2015;Gabbett et al, 2012;Twist et al, 2014), collisions (Oxendale et al, 2015) and, more recently, metabolic power (Kempton et al, 2015). Data on TEE are however limited despite such data having clear potential to inform appropriate training loads to maximise performance (Fowles, 2006), body composition (Morehen et "The Assessment of Total Energy Expenditure During a 14-day 'In-Season' Period of Professional Rugby League Players Using the Doubly Labelled Water Method" by Morehen JC et al International Journal of Sport Nutrition andExercise Metabolism © 2016 Human Kinetics, Inc.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 There was also a non-linear decline in countermovement jump performance across the 22-day cycle that was indicative of an accumulated neuromuscular fatigue. While flight time was shorter than before Match 1 at all time points, the most notable reduction occurred around Match 2 and Match 3.…”
mentioning
confidence: 99%
“…1,2 These activities are known to lead to immediate and prolonged fatigue in elite players, 3,4 observed as losses in muscle function and increases in perceived soreness and fatigue that remain for up to four days after a match. 3,4,5 Players therefore require appropriate between-match recovery to minimize the negative effects of fatigue on performance.…”
Section: Introductionmentioning
confidence: 99%